2018
DOI: 10.2478/humo-2013-0033
|View full text |Cite
|
Sign up to set email alerts
|

Body satisfaction and time spent on physical activity in Polish students

Abstract: PurposeThe aim of this study was to assess the relationship between body satisfaction, the amount of time spent on physical activity (PA), and body mass index (BMI) in a group of young adults.MethodsA sample of 527 students (351 females and 176 males) aged 19-24 years were recruited for analysis. Measures of height and weight were collected. Participants completed a questionnaire about PA performed during the previous seven days, intention of increasing PA levels, overall body satisfaction, their ideal BMI, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Most active were students in primary schools, with university students being the least active [29]. We report a higher percentage of college students exercising and in line with other studies [30,31], young men in our study population were more active than young women. This could be explained by cultural norms and trends in Cyprus, where joining a gym on a regular basis has increased in popularity among young adults, especially men.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Most active were students in primary schools, with university students being the least active [29]. We report a higher percentage of college students exercising and in line with other studies [30,31], young men in our study population were more active than young women. This could be explained by cultural norms and trends in Cyprus, where joining a gym on a regular basis has increased in popularity among young adults, especially men.…”
Section: Discussionsupporting
confidence: 92%
“…A birth cohort study in 4100 subjects aged between 22 and 23 years in Brazil showed that the prevalence of body dissatisfaction reached 64%, with 42% of the subjects reporting feeling larger and 22% reported feeling smaller than the desired body size [41]. It would seem that body dissatisfaction is pervasive among young adults and as perhaps expected, is a particular issue for young women, with more women than men desiring a body shape slimmer than their current one [31,42]. While body dissatisfaction may start even before adolescence, longitudinal studies have shown that body dissatisfaction increases between middle and high school and increases even further during the transition to young adulthood [43], making this an important period for future perceptions and self-confidence.…”
Section: Body Imagementioning
confidence: 94%
“…The sociocultural theory purports that mass media influence an individual's perceptions of what the ideal body is [18]; yet, it is also influenced by a culturally defined standard of beauty or ideal of beauty [19].…”
Section: Association Between Body Image and Healthy Lifestylementioning
confidence: 99%
“…Physical inactivity is closely related to negative body image attitudes and perceptions and is the most significant health threat (Blair, 2009). Physical activity is one of the most significant elements that positively impacts body satisfaction.Body satisfaction is a critical component of young adults' psychological distress and life satisfaction because young adults are under considerable social and peer pressure to conform to societal images of attractiveness and emulate the cultural ideal (Olchowska-Kotala & Chromik, 2013). Rudd and Lennon's (2000) qualitative study of body image indicated that clothing was mentioned as a way to camouflage an aspect of the body perceived as flawed or as a means of self-expression among female college students.…”
mentioning
confidence: 99%